2016
DOI: 10.1038/srep25359
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and kinetic analysis of viral shedding and immunological responses in MERS patients representing a broad spectrum of disease severity

Abstract: Despite the ongoing spread of MERS, there is limited knowledge of the factors affecting its severity and outcomes. We analyzed clinical data and specimens from fourteen MERS patients treated in a hospital who collectively represent a wide spectrum of disease severity, ranging from mild febrile illness to fatal pneumonia, and classified the patients into four groups based on severity and mortality. Comparative and kinetic analyses revealed that high viral loads, weak antibody responses, and lymphopenia accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
300
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(341 citation statements)
references
References 35 publications
27
300
1
5
Order By: Relevance
“…They were observed in the very early course of the illness, indicating that inflammation had already been enhanced. Lymphopenia and thrombocytopenia presenting from the initial presentation of severe MERS-CoV infected patients were also observed in the recent report by Min et al 25 Although time of measurements were not specifically described, these laboratory abnormalities were previously observed in severe MERS cases and other respiratory viral illnesses including severe acute respiratory syndrome (SARS) and influenza, which are caused by intense inflammatory response to the viruses. 15,26e33 This is the first report that identified these laboratory findings as predictive factors for pneumonia development and progression to respiratory failure in MERS.…”
Section: Discussionsupporting
confidence: 53%
“…They were observed in the very early course of the illness, indicating that inflammation had already been enhanced. Lymphopenia and thrombocytopenia presenting from the initial presentation of severe MERS-CoV infected patients were also observed in the recent report by Min et al 25 Although time of measurements were not specifically described, these laboratory abnormalities were previously observed in severe MERS cases and other respiratory viral illnesses including severe acute respiratory syndrome (SARS) and influenza, which are caused by intense inflammatory response to the viruses. 15,26e33 This is the first report that identified these laboratory findings as predictive factors for pneumonia development and progression to respiratory failure in MERS.…”
Section: Discussionsupporting
confidence: 53%
“…These findings imply that MERS-CoV could be transmitted frequently during the early course of the disease. A recent virus shedding study showed that MERS-CoV titers in sputum samples were around 10 8 copies per milliliter as early as 3 days after symptom onset, while the viral shedding kinetics of the SARS-CoV infection was an inverted V shape, with its sharp peak around day 10 (13). These findings suggest that control of a MERS-CoV outbreak would be more difficult than that of a SARS-CoV outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Another study classified MERS patients ( n = 14) according to disease severity and mortality and found sustained viremia in plasma of all fatal ( n = 5, average of 32,000 copies/mL) and severe cases ( n = 4). In contrast, less severe cases had stronger antibody responses, less lymphopenia, and either no viremia or they cleared plasma until day 18 after symptom onset [9]. Also, it was reported ( n = 21) that patients without traceable blood MERS-CoV on admission had a survival rate of about 90% ­compared to 40% in blood viral RNA-positive patients [10].…”
Section: Discussionmentioning
confidence: 99%